Effect of Group Setting on Gross Motor Performance in Children 3–5 Years Old with Motor Delays. (1st January 2017) - Fay, Deanne; Wilkinson, Tawna; Wagoner, Michelle; Brooks, Danna; Quinn, Lauren; Turnell, Andrea
ABSTRACT: Aims : The purpose of this study was to evaluate differences in gross motor performance of children 3–5 years of age with motor delays when assessed individually compared to assessment in a group setting among peers with typical development (TD). Methods : Twenty children with motor delays and 42 children with TD were recruited from a preschool program. A within-subject repeated measures design was used; each child with delay was tested both in an individual setting and in a group setting with two to four peers with TD. Testing sessions were completed 4–8 days apart. Ten different motor skills from the Peabody Developmental Motor Scales-2 were administered. Performance of each item was videotaped and scored by a blinded researcher. Results : Overall gross motor performance was significantly different ( p < .05) between the two settings, with 14 of 20 children demonstrating better performance in the group setting. In particular, children performed better on locomotion items ( p < .05). Conclusions : The higher scores for locomotion in the group setting may be due to the influence of competition, motivation, or modeling. Assessing a child in a group setting is recommended as part of the evaluation process.